Characteristics of older autistic adults: a systematic review of literature - Tse, VWS; Lei, J; Crabtree, J; Mandy, W; Stott, J (Springer, 2021)
Autism is a neurodevelopmental condition that affects individuals across their lifetime, though the effects of ageing in older adulthood are poorly understood to date. This systematic review assessed six characteristics in older autistic adults (cognitive functioning, co-occurring difficulties, autism symptom severity, social integration, adaptive functioning, language processing). A total of 41 studies met inclusion criteria, 16 of which included autistic adults with intellectual disability, and three were longitudinal in nature. Findings show differing effects of ageing across the six domains. Factors contributing to discrepancies such as age and IQ differences, methodology and healthy survivor effect are discussed. The need for more longitudinal studies to investigate changes across developmental stages alongside other limitations, future directions and clinical implications are discussed.